Simultaneous Determination of Thidiazuron and Forchlorfenuron in Orange by Solid Phase Extraction with Molecularly Imprinted Membrane Followed by High Performance Liquid Chromatography - SHI Yu, WANG Jian, DOU Rui, QI Yingchun, DONG Xiao, NIU Zhirui, REN Jingyu, HUANG Hua, ZHAO Yixue (Shipin Kexue)
In this study, molecularly imprinted membrane (MIM) was prepared using polydopamine (PDA)-modified polyvinylidene fluoride (PVDF) membrane as the base membrane, thidiazuron (TDZ) as the template, methacrylic acid (MAA) as the functional monomer, and ethylene glycol dimethacrylate (EGDMA) as the cross-linker. This adsorption material was applied to the highly selective simultaneous extraction of TDZ and its structural analogue forchlorfenuron (CPPU) from orange. Scanning electron microscope (SEM) characterization of the prepared samples showed that the surface of the three-dimensional network structure of the PDA@PVDF membrane was coated with dense molecularly imprinted polymers. The performance tests showed that the adsorption capacity of MIM for TDZ and CPPU was 1.80 and 1.89 times as high as that of the non-imprinted counterpart, reaching adsorption equilibrium after 20 and 30 min, respectively. The specificity parameters for the interfering substances coumarin and 3-tert butylphenol were determined to be 23.2 and 19.3, respectively. MIM was successfully applied for the simultaneous extraction of TDZ and CPPU from orange samples. At spiked concentrations of 2.0, 3.0 and 5.0 µmol/L, the spiked recoveries of MIM extraction combined with high performance liquid chromatography (HPLC) for TDZ and CPPU ranged from 90.3%–99.4% and 88.2%–98.1%, respectively, with relative standard deviations in the range of 0.9%–2.5% and 1.2%–3.0% (n = 3), respectively. The developed method had the advantages of simplicity, high sensitivity, precision and recoveries, and low cost and was suitable for the detection of TDZ and CPPU residues in fruits and vegetables.